2023
DOI: 10.1007/s12633-023-02290-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alumina Modified by Silane on the Mechanical, Swelling and Dielectric Properties of Al2O3/EPDM/SBR Blend Composites

Abstract: Rubber blending has been widely used to improve various properties in finished rubber products. The purpose of this paper is to investigate the effect of filler size, type, concentration, and surface treatment on the mechanical, swelling, dielectric, and morphology properties of ethylene propylene diene rubber (EPDM)/styrene-butadiene rubber (SBR) rubber blend nanocomposites filled with alumina (Al2O3) nanoparticles. Bis-(3-(triethoxysilyl)-propyl)-tetrasulfide (TESPT) was used as a silane coupling agent. Rubb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…It is obvious from the data that the equilibrium swelling percentage ( Q ) begins high at the blank NBR composite (131%), and then it decreases by addition of 1 phr of TMQ (117%), 1 phr of RC (116%), and 2 phr of RC (105%) antioxidants. This decrease may be attributed to the strong crosslinks formed during curing preventing the solvent from passing through the inner structure of rubber compounds leading to low swelling 30 . The molecular weight (Mc) between crosslinks is given in Data S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is obvious from the data that the equilibrium swelling percentage ( Q ) begins high at the blank NBR composite (131%), and then it decreases by addition of 1 phr of TMQ (117%), 1 phr of RC (116%), and 2 phr of RC (105%) antioxidants. This decrease may be attributed to the strong crosslinks formed during curing preventing the solvent from passing through the inner structure of rubber compounds leading to low swelling 30 . The molecular weight (Mc) between crosslinks is given in Data S1.…”
Section: Resultsmentioning
confidence: 99%
“…This decrease may be attributed to the strong crosslinks formed during curing preventing the solvent from passing through the inner structure of rubber compounds leading to low swelling. 30 The molecular weight (Mc) between crosslinks is given in Data S1. NBR containing 2 phr of RC shows the lowest Mc (881.45 g/mole).…”
Section: Swelling Properties and Crosslink Density Of The Prepared Nb...mentioning
confidence: 99%
“…Blank rubber composite is the most swelled while rubber composite (3c) is the least swelled in toluene as represented in Figure 10. Due to further crosslinks formed during curing by the presence of polyanilines in rubber composites, it becomes difficult for toluene to penetrate through the gaps present between rubber chains resulting in low swelling percent 28 . Crosslink density is the opposite of equilibrium swelling; hence, rubber composite (3c) is the most crosslinked, while blank is the least crosslinked one as illustrated in Figure 11.…”
Section: Resultsmentioning
confidence: 99%
“…Figures 14(b) and (c) at room temperature also depict the effects of molar mass/molecular weight on aliphatic and chlorinated penetrants on the MPU by silicone rubber/mHNTs nanotubes. Prior studies [82] have shown that solvent absorption decreases with increasing molar mass/molecular weight of both aliphatic and aromatic penetrants. Dichloromethane in particular demonstrates lower equilibrium absorption than n-pentane in aliphatic solvents and lower equilibrium intake than chloroform in chlorinated solvents.…”
Section: Figure 10 Abrasion Loss Of Silicone Rubber Nanocompositesmentioning
confidence: 92%